Co-Crystals for Drug Design: A Logical Approach for Modifying Physicochemical Properties of Drugs - Габа, пуном; Пиплан, Мона; Шарма, Шаилеш (Scripta Medica, 2026)
Drug design plays a critical role in the pharmaceutical industry, addressing the limitations of many compounds with medicinal properties that cannot serve as an effective active pharmaceutical ingredient. Extensive research has been conducted to overcome this challenge, with co-crystals emerging as a promising solution. In drug design, APIs often face challenges such as low solubility, poor mechanical properties, or degradation risks. Since the discovery of co-crystals, their potential applications have expanded significantly. Initially recognised as simple solubility modifiers, recent research emphasises their diverse uses, including flavour masking and the enhancement of mechanical properties. With the commercialisation of co-crystal-based drugs, research has shifted from their potential applications to optimise production methods. This article reviews key production methods, including solvent evaporation and hot-melt extrusion, which enable scalable and ecologically sustainable co-crystal synthesis. Addressing poor physicochemical properties, especially low bioavailability, remains a persistent challenge in pharmaceutical development. Co-crystals present an innovative and efficient solution. An active pharmaceutical ingredient (API) and a co-former are joined by non-covalent interactions to form co-crystals, which are crystalline solids. These structures maintain the natural pharmacological efficacy of pharmaceuticals while improving their physicochemical characteristics, such as stability and solubility. They provide a systematic and rational approach to improve API properties because their design follows well-established crystal engineering principles. This review emphasises the increasing interest in co-crystals and their importance in crystal preparation methods. Co-crystallisation has improved the stability, dissolution rate and solubility of active pharmaceutical ingredients. Although, there are challenges related to scalability, innovative solutions are necessary to ensure consistent and cost-effective production. With ongoing research and advancements in scalable manufacturing, co-crystals are poised to revolutionise pharmaceutical development by overcoming bioavailability challenges and enhancing therapeutic outcomes.